Inflexible eye fixation pattern in schizophrenia affecting decision-making on daily life. (April 2019) - Kim, Soo-Jeong; Hong, Yeon-Ju; Kim, Min-Woo; Jung, Young-Hoon; Min, Sa-Rang; Kim, Jae-Jin
Highlights: Patients with schizophrenia made purchase decisions at a higher rate. Patients showed shorter fixation on clothing or faces during purchase decisions. In patients, fixation time ratio did not change over purchase decisions. In controls, fixation time ratio was higher in not-to-buy than to-buy decisions. Aberrant decision-making behaviors are closely related to inflexible gaze patterns. Abstract: Patients with schizophrenia have difficulties in real life due to impairment in ability to make decisions. The purpose of this study was to elucidate the relationship between impaired decision-making processes with real life stimuli and abnormal eye gaze patterns in patients with schizophrenia. Each of 23 patients with schizophrenia and 23 healthy controls performed an apparel purchase decision task including the influencing factors such as preference, fit, and price, during which the eye gaze was traced. Fixation time and fixation time ratio on areas of interest, which were set for participant faces and clothing, were compared between the two groups. Compared with controls, patients made purchase decisions at a higher rate and showed significantly shorter fixation time on clothing in the preference, fit, and price phases and on faces in the purchase phase. Fixation time ratio of face over clothing did not change over purchase decisions in patients, whereas controls showed significantly higher fixation time ratio in not-to-buy decisions than in to-buy decisions. These results suggest that aberrant decision-making behaviors in patients with schizophrenia are closely related to inflexible visual information gathering patterns because they apportion the same amount of attention to objects regardless of purchase intention.